Наши сказки: сказки любимых писателей / худож. Л. Непомнящий - Непомнящий Л. (Как хорошо уметь читать!, 2010)
Экземпляры: М/а ДБ (20111031) / Инвентарный номер: 97568 / Цена: 173.52 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 37 / ББК: 84(2Рос=Рус)6